Proposição de um modo de entrada nos Emirados Árabes Unidos: um estudo de caso da Sierra Móveis - Cristofolli, Matheus (Universidade do Vale do Rio dos Sinos, 2018)
The present study sought to analyse the most appropriate entry mode in the United Arab Emirates for Sierra Móveis Ltda., a Brazilian furniture manufacturer. This is a descriptive and qualitative case study. In this regard, open and semi-structured interviews, as well as questionnaires, were applied to eight informants - five from the inside and three from the outside of the company: export, sales and communication managers; export and import supervisor; export assistant; executive director of a fur niture exportation project; CEO (Chief Executive Officer) of a company specialized in the Middle East market; and an Executive of a Brazilian bank with operation in the United Arab Emirates. In addition to the interviews and the questionnaire, were used as data collection techniques the documents analysis and the direct observation. Therefore, it was verified as the main findings of this research that Sierra Móveis Ltda. is in a constant process of internationalization and the company has capacity and know-how to expand its brand to markets that have not yet been fully mastered, as well as products with global characteristics. It was also noticed that the nation of the United Arab Emirates is open to foreign investments and, in spite of the cultural differences compared to the western lifestyle, it is a country which demonstrates ease of doing business; it has a diversified population that is accustomed to imported products as well as a stable and bland political environment, good economic indica tors and low costs for investments and importation, mainly if the merchandise is des tined to a free zone. Thus, it was observed that the most adequate entry mode for Sierra Móveis in the United Arab Emirates is by means of a direct investment in the Jebel Ali Free Zone, keeping the production of their furniture in Brazil to guarantee their quality. After the furnishing is ready it will be exported directly for the enterprise in the Arab country.
Keywords: Emirados Árabes Unidos; Móveis; Modos de entrada no exterior; Investimento direto no exterior; Zona Franca; United Arab Emirates; Furniture; Modes of foreign entry; Foreign direct investment; Free zone